A multicenter, descriptive epidemiologic survey of the clinical features of spinal metastatic disease in China. (1st September 2020) - Zhang, Hao-Ran; Qiao, Rui-Qi; Yang, Xiong-Gang; Hu, Yong-Cheng
ABSTRACT: Objective: Spinal metastases have unique epidemiological features and treatment methods. Unfortunately, the relative scarcity of spinal metastases has limited the widespread development of descriptive epidemiological studies, especially in Asian countries. The purpose of this study was to describe the epidemiological characteristics of patients with metastatic spinal tumors in China between 2007 and 2019. Methods: From January 2007 and July 2019, data on patients with spinal metastases were collected from five cancer centers in China, and demographic characteristics, primary tumor types, segments and numbers of vertebral lesions, disease-related scores, and treatment methods were reviewed. Results: A total of 2228 patients with spinal metastases were reviewed in this study, including 1279 male patients and 949 female patients, and the male to female ratio was 1.35: 1. More than half of patients developed metastatic diseases between the ages of 50 years and 69 years (64%). Overall, lung cancer (824 cases, 37%) was the most common primary tumor type and the most common level of spinal involvement was multi-level of metastases (860 cases, 39%). 705 patients (32%) had undergone surgical treatments, 1028 patients (46%) had undergone radiotherapy for metastatic vertebrae, and 855 patients (38%) had received systemic treatments. The age, primary tumor type, number of involved vertebrae, Frankel grade, and spinal instability neoplastic score would affect the surgical decision-making. Discussion: This study provides insight into the epidemiological characteristics of spinal metastasis and health care service utilization in spinal metastasis patients in China. Abbreviations: ICD-10: International Classification of Disease, Tenth Revision; VAS: Visual Analogue Scale; KPS: Karnofsky Performance Status; SINS: Spinal Instability Neoplastic Score; SOSG: Spine Oncology Study Group; MRI: Magnetic Resonance Imaging; CT: Computed Tomography; ECT: Emission Computed Tomography.